Political Connections and Gender Diversity: Exploring Corporate Risk - Alkadi, Rotana S.; Muhandes, Rawaa F. (International Journal of Economics and Financial Issues, 2025)
Employing panel data of US firms (1992-2018), we examine total risk for politically connected firms, formed through campaign contributions, and whether these connections impact the negative association between female presence in the TMT and total risk. The results show that corporate political connections are related to lower total, systematic, and idiosyncratic risk. Their interaction with TMT gender diversity further reduces total risk, by lowering idiosyncratic risk. This suggests that political connections have more profound benefits by influencing asset prices, as a non-market strategy reducing stock returns volatility. They also strengthen and complement the negative association between TMT gender diversity and total risk.